Serum Procalcitonin and Proinflammatory markers in Polycystic Ovary Syndrome - Göde, Funda; Yücesoy, Fulya; Sağlam, Aylin; Akarsu, Süleyman; Örem, Asım; Sharafkhanov, Khayal (Gynecology Obstetrics & Reproductive Medicine, 2017)
Objective: We evaluated levels of procalcitonin and proinflammatory markers in patients with polycystic ovary syndrome (PCOS) and compared them with controls in the Black Sea region of Turkey. Study Design: This prospective controlled study involved patients with PCOS (n=59) and healthy age-matched controls (n=26; total, n=85). Serum procalcitonin (PCT), white blood cells (WBCs), high-sensitivity C-reactive protein (h-CRP), homocysteine (Hcy) levels, insulin resistance, and lipid profiles were compared between the PCOS and control groups. The same parameters were also compared between overweight and normal-weight PCOS patients. Results: Serum PCT, Hcy, h-CRP, and WBC levels were similar in the PCOS and control groups. High-density lipoprotein (HDL) levels were lower in the PCOS group than in the control group (p <0.05). In a subgroup analysis of the PCOS group, there were no significant differences between overweight and normal-weight PCOS patients with regard to proinflammatory markers (serum WBC, h-CRP, Hcy, PCT levels). However, total cholesterol, LDL, and triglyceride levels were significantly higher in overweight PCOS patients (p <0.005). Serum HDL levels were significantly lower in the overweight PCOS group than in the normal-weight group (p <0.005). Fasting insulin and HOMA-IR levels were significantly higher in overweight PCOS than normal-weight PCOS patients (p<0.05). Conclusions: Serum PCT, h-CRP, WBC, and Hcy levels were within normal ranges in PCOS patients. These results may be related to the relatively young age and regional differences in the study group.